2006
DOI: 10.1002/qua.21090
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of blue‐shifted hydrogen bond versus conventional hydrogen bond in methyl radical complexes

Abstract: ABSTRACT:Methyl radical complexes H 3 C . . . HCN and H 3 C . . . HNC have been investigated at the UMP2(full)/aug-cc-pVTZ level to elucidate the nature of hydrogen bonds. To better understand the intermolecular H-bond interactions, topological analysis of electron density at bond critical points (BCP) is executed using Bader's atoms-in-molecules (AIM) theory. Natural bond orbital (NBO) analysis has also been performed to study the orbital interactions and change of hybridization. Theoretical calculations show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
11
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 24 publications
2
11
0
Order By: Relevance
“…Single-electron halogen bonds are very rare and have been much less studied than single-electron hydrogen bonds such as CH 3 ⋅⋅⋅HF [11], CH 3 ⋅⋅⋅HX (X = Cl, Br) [12], CH 3 ⋅⋅⋅H 2 O [13], CH 3 ⋅⋅⋅ CH 4 [14], CH 3 ⋅⋅⋅HCN and CH 3 ⋅⋅⋅HNC [15]. The few theoretical studies of single-electron halogen bonds that have been reported to date have concentrated on the structure-activity relationships between the strength of interaction and the nature of the substituents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Single-electron halogen bonds are very rare and have been much less studied than single-electron hydrogen bonds such as CH 3 ⋅⋅⋅HF [11], CH 3 ⋅⋅⋅HX (X = Cl, Br) [12], CH 3 ⋅⋅⋅H 2 O [13], CH 3 ⋅⋅⋅ CH 4 [14], CH 3 ⋅⋅⋅HCN and CH 3 ⋅⋅⋅HNC [15]. The few theoretical studies of single-electron halogen bonds that have been reported to date have concentrated on the structure-activity relationships between the strength of interaction and the nature of the substituents.…”
Section: Introductionmentioning
confidence: 99%
“…However, previous studies of unusual lithium and halogen bonds, especially the latter, have been very limited [10]. Most recently, the concept of single-electron weak interactions has been introduced to characterize several special weak bonds, including single-electron hydrogen bonds [11][12][13][14][15], single-electron lithium bonds [16], single-electron sodium bond [17] and singleelectron halogen bonds [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The weakly hydrogen-bonded H 3 C-HF complex has been detected in the reaction of methane with F 2 in low-temperature noble gases using spectroscopic methods [13][14][15]. The structures, frequency shifts, and interaction energies of H 3 C-HF, H 3 C-HCCH, H 3 C-HCN, H 3 C-HNC, and H 3 C-H 2 O complexes have been investigated using quantum chemical calculations [8,[16][17][18][19][20][21]. The results show that the methyl radical can participate in singleelectron hydrogen bonding, but the bonding is relatively weak.…”
Section: Introductionmentioning
confidence: 99%
“…Most recently, the concept of single‐electron H bond, i.e, the interaction between the unpaired electron in the radical molecule and the proton donor, has been introduced to characterize several special hydrogen bond complexes11–20. As sodium is a congener of hydrogen, it is a logical isomorphic replacement to substitute the hydrogen with sodium in single‐electron hydrogen bond.…”
Section: Introductionmentioning
confidence: 99%